2018
DOI: 10.1111/adj.12649
|View full text |Cite
|
Sign up to set email alerts
|

Medical emergencies in dental practice – management requirements and international practitioner proficiency. A scoping review

Abstract: The management of medical emergencies is widely considered a requisite skill for all dentists. Timely intervention of an emergency can significantly alter the outcome for a patient's morbidity and possible mortality. This scoping review examines the prevalence of medical emergencies in dental practice, as well as dentists' attitude, confidence, and competence, of medical emergency management within a dental setting. Key findings include a lack of preparedness towards medical emergencies, despite a universal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 33 publications
1
23
1
7
Order By: Relevance
“…As dentists are typically the most senior medical staff in their practice, the responsibility falls upon them to provide initial stabilisation of a patient's medical condition, yet all staff should be trained proportionally to their level of clinical responsibility and up-to-date with the latest relevant guidelines. A recent Australian scoping review highlighted that dentists may not be fully prepared for such events (13), which is consistent with previous research suggesting that many dentists may lack appropriate knowledge or clinical aptitude (10,14). All Australian dental schools currently require their students to undertake first aid or basic life support certification prior to undertaking clinical placement.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…As dentists are typically the most senior medical staff in their practice, the responsibility falls upon them to provide initial stabilisation of a patient's medical condition, yet all staff should be trained proportionally to their level of clinical responsibility and up-to-date with the latest relevant guidelines. A recent Australian scoping review highlighted that dentists may not be fully prepared for such events (13), which is consistent with previous research suggesting that many dentists may lack appropriate knowledge or clinical aptitude (10,14). All Australian dental schools currently require their students to undertake first aid or basic life support certification prior to undertaking clinical placement.…”
Section: Introductionsupporting
confidence: 54%
“…Notably, this is significantly higher than rates found in studies of similar design and population from the late 1990s which reported emergencies occurring closer to one event every 3.6-4.5 years (12), and appears consistent with rising trends. No evidence exists within Australia from the past 22 years (13). As dentists are typically the most senior medical staff in their practice, the responsibility falls upon them to provide initial stabilisation of a patient's medical condition, yet all staff should be trained proportionally to their level of clinical responsibility and up-to-date with the latest relevant guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…A Dutch study reported an occurrence of 0.75 medical emergencies per dentist per year [ 2 ]. In a scoping review on medical emergencies in dental practice, it is reported that 43.6 to 75% of dentists will be required to perform some form of medical emergency management throughout their career [ 3 ]. Although life-threatening medical emergencies are rare in dental practice, according to Collange et al, approximately 5% of general practitioners have to cope with cardiopulmonary resuscitation (CPR) at least once during their career [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the dental and orthodontic team are expected to adequately manage common acute medical emergencies that might occur. Nevertheless, dentists still lack skills for managing medical emergencies regardless of the incorporation of medical training into dental curricula [ 3 , 5 , 6 ]. Moreover, only 69% of dentists feel comfortable managing medical emergencies in a dental setting [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical knowledge derived from lectures, tutorials and exams may not adequately prepare the dental practitioner. Simulation training with hands on involvement may better facilitate memory retention and is commonly reported to be the preferred modality of education [3,8,10,13,14]. Table 1.…”
Section: Introductionmentioning
confidence: 99%